2006
DOI: 10.1007/s10620-006-3197-9
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Epithelial Growth of the Small Intestine in the Rat Occurs by Both Crypt Fission and Crypt Hyperplasia

Abstract: Studies of growth of the small intestine have largely concentrated on crypt hyperplasia rather than crypt fission. The aim of this study was to investigate quantitatively both crypt fission and crypt hyperplasia. DAxPVG/c rats were killed at 7, 11, 14, 17, 19, 21, 25, 55, and 72-73 days of life. Samples of jejunum at one third of the intestinal length were taken for morphometry (villous area, crypt area, percentage of bifid crypts, and crypt mitotic count) by microdissection. Growth factors and their receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
5
30
0
2
Order By: Relevance
“…A major difference in the enteroid system is the high frequency of crypt fission events. We estimate that ϳ5% of crypts freshly isolated from WT murine proximal small intestine show evidence of crypt fission, which is consistent with observations in other species (14,15), whereas multiple crypt fission events in the enteroid cultures are observed during the period 3-8 days postplating. Newly forming crypts are readily recognized as "buds" from existing crypts and therefore can be avoided or specified for study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A major difference in the enteroid system is the high frequency of crypt fission events. We estimate that ϳ5% of crypts freshly isolated from WT murine proximal small intestine show evidence of crypt fission, which is consistent with observations in other species (14,15), whereas multiple crypt fission events in the enteroid cultures are observed during the period 3-8 days postplating. Newly forming crypts are readily recognized as "buds" from existing crypts and therefore can be avoided or specified for study.…”
Section: Discussionsupporting
confidence: 90%
“…In a study validating the putative stem cell marker, leucine-rich repeatcontaining G-protein-coupled receptor 5 (Lgr5), it was shown that freshly isolated small intestinal crypts placed in collagen gels with specific growth factors would form self-organizing crypt organoids (enteroids). Crypts seal at the open end and begin a process whereby new crypts are formed by a process similar to crypt fission in vivo (14,15). The enteroid epithelial cells migrate from the crypt to a central epithelial-lined cavity (villus-like domain) where they are eventually shed in an apoptotic process.…”
mentioning
confidence: 99%
“…1B); pups began to acquire resistance from day 3 and were completely resistant by day 9. Reductions in susceptibility to infection following colonization will be accompanied by structural, physiological, and microbiological changes of GI tract tissues (29,30), and we therefore undertook parallel histological and immunohistochemical investigations of GI tissue in order to ensure that processes that affect susceptibility to infection can be correlated with the dynamic process of postnatal development of the rat intestine. Over the P2-to-P9 period, the length of the digestive system (stomach to colon) increased in an incremental fashion from a mean of 25.6 cm at P2 to 47.6 cm at P9 and was characterized by rapid postnatal physi- ological and anatomical development due to expansion of the small intestine and increased differentiation of the cecum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case in the intestine in which new crypts are produced by fission of existing ones. This phenomenon likely plays a role in the elongation of the bowel during postnatal growth, but it is not observed in response to injury, suggesting that it might be under control of GH levels, an autonomous program, or both (Cummins et al 2006).…”
Section: Organ Growth Is Driven By Two Distinct Cellular Processesmentioning
confidence: 99%